New Insights in the Use of a Strong Cationic Resin in Dye Adsorption - Sanchez-Poblete, J; Oyarce-Riveros, E (IWA Publishing, 2020)
The adsorption of methyl orange (MO) in aqueous solution was evaluated using a cationic polymer (Amberlite IRA 402) in batch experiments under different experimental variables such as amount of resin, concentration of MO, optimum interaction time and pH. The maximum adsorption capacity of the resin was 161.3 mg g-1 at pH 7.64 at 55 °C and using a contact time of 300 min, following the kinetics of the pseudo-first-order model in the adsorption process. The infinite solution volume model shows that the adsorption rate is controlled by the film diffusion process. In contrast, the chemical reaction is the decisive step of the adsorption rate when the unreacted core model is applied. A better fit to the Langmuir model was shown for equilibrium adsorption studies. From the thermodynamic study it was observed that the sorption capacity is facilitated when the temperature increases. © IWA Publishing 2020.